Faktor-faktor yang Berhubungan dengan Praktek Sanitasi Lingkungan Bersih dan Sehat Melalui 'PHBS' pada Siswa Sekolah Dasar di Kecamatan Banyumanik - Istiarti, Tinuk; Dangiran, Hanan Lanang (Master Program of Environmental Health, Faculty of Public Health, Diponegoro University, 2016)
Title : The factors Related to The Sanitation Practice through Clean and Healthy Life Behaviour on Elementary School Students at Banyumanik DistrictBackground: The high rate of diarrhea incident in Semarang, especially on elementary school students, needs a special attention. The incident rate in the area of Banyumanik district shows a high level compared to those of other working areas. The incident rate of 5-14 year ages shows an increase from 2013 to 2015, from 142 to 187 and to 289 cases. Clean and healthy environment sanitation through â€œPHBSâ€ seems to be the simple way to a self protection against various diseases. Based on the - background mentioned above, the research was conducted to analyze the factors relating to the sanitation practice of clean and healthy environment through â€œPHBSâ€. Method: This research was conducted by using descriptive analysis with a quantitative approach. The research samples were taken using random sampling of 72 elementary school students from 11 elementary schools at Banyumanik district. Results: The research result showed that 68,1% of the respondents experienced a good practice and 31,9% experienced a not-so-good practice. The statistical analysis showed that there was a correlation between knowledge of clean and healthy sanitation environment (p-value = 0,019) and attitude (p-value = 0,029) toward the practice of clean and healthy sanitation environment.Conclusion: Level of knowledge was able to increase attitude toward practice of clean and healthy sanitation environment.Â